Stress and depressive symptoms in university students in Hong Kong under the pandemic: Moderating effect of positive psychological attributes - Daniel T. L. Shek; Wen-yu Chai; Tingyin Wong; Kaiji Zhou (Frontiers in Psychology, 2023)
IntroductionThere are very few studies examining the psychological well-being of university students in Hong Kong under the COVID-19 pandemic. Besides COVID-19-related stress, the “social event” in 2019-2020 has caused significant stress in young people. As such, we attempted to answer several research questions in this paper. First, what are the relationships between stresses (COVID-19 and “social event” related stresses) and psychological well-being indexed by depressive symptoms? Based on the stress and coping perspective, we predicted that there would be positive relationships between both types of stress and depression. Second, what are the relationships between different positive psychological factors (including life satisfaction, resilience and emotional management, flourishing, and beliefs about adversity) and depression? Based on different theoretical models of positive psychology, we hypothesized that negative relationships would exist between positive psychological factors and depressive symptoms. Third, do positive psychological attributes moderate the associations between stresses (COVID-19 and “social event” related stresses) and depressive symptoms? Based on the positive psychology literature, we hypothesized that positive psychological attributes would buffer the negative impact of stresses on depression.MethodsWe recruited university students roughly one year after the first wave of the pandemic (N = 1,648) in early 2021. We used 25 items to measure COVID-19-related stress and “social event” related stress. For psychological well-being indexed by depressive symptoms, we used the “Centre for Epidemiologic Studies Depression Scale Revised (CESD-R)”. For positive psychological attributes, we employed established measures of life satisfaction, resilience and emotional management, flourishing, and beliefs about adversity.ResultsRegarding the relationship between stress and depression, we found positive relationships between both types of stress and depressive symptoms. As predicted, negative relationships existed between all positive psychological attributes and depressive symptoms. Besides, the positive psychological attributes significantly moderated the effects of stresses on depression, suggesting that these factors can reduce the negative impacts of stresses on depression. The present findings provide support for those models, highlighting the importance of positive psychological attributes as protective factors for university students’ depression.DiscussionThe findings of this study underscore the important role of positive psychological attributes in the stress-depression relationship in university students under the pandemic. The findings also generalize the positive youth development theory in the Chinese context. In terms of practice, university administrators and service providers should consider cultivating positive psychological attributes in university students with the purpose of promoting their psychological well-being.